Ten New Insights in Climate Science 2024 - Schaeffer, Roberto; Schipper, Lisa; Ospina, Daniel; Mirazo, Paula; Alencar, Ane; Anvari, Mehrnaz; Artaxo, Paulo; Biresselioglu, Mehmet Efe; Biome, Tanja; Boeckmann, Melanie; Brink, Ebba; Broadgate, Wendy; et al. (2024)
Climate change research is broad, diverse and constantly growing. Cross- and interdisciplinary understanding is essential for generating robust science advice for policy. However, it is challenging to prioritise and navigate the ever-expanding peer-reviewed literature. To address this, we gathered input from experts across various research fields through an online questionnaire and prioritised a set of 10 key research advances with high policy relevance. This year, we focus on: (1) Declining aerosol emissions, (2) soaring methane emissions, (3) concerning ocean dynamics, (4) diversity and resilience of Amazon forests, (5) expanding risk of “uninhabitability”, (6) climate impacts to maternal and reproductive health, (7) climate-resilient development for cities, (8) vulnerability of critical infrastructure, (9) governance of the energy transition minerals value chain, and (10) public acceptance of climate policies. This science synthesis and science communication effort is also the basis for a policy report which aims to elevate climate science every year ahead of the UN Climate Summit.